Healthcare Simulation Dictionary (2nd.ed 2.1) - Dev Nath, Kaushal (Society for Simulation in Healthcare & Agency for Healthcare Research and Quality (AHRQ), 2024)
Healthcare Simulation Dictionary was originally published by The Society for Simulation in Healthcare (SSH) under the license of The Agency for Healthcare Research and Quality (AHRQ) in 2020.